SlideNoter - Developing a notepad application for Android tablets - Moberg, Robert; Aldenvik, Patrik; Pelling, Alex; Scholander, Jonas (My University, 2012)
This report presents the process and thoughts behind the development of an open source Android application; an application for reading PDF-files and adding notes upon them. The main purpose is to provide an alternative for students, enabling them to take notes during lectures without pen and paper. The report covers the basic building blocks of the Android graphical user interface, blocks that the application use, as well as the integrated PDF-reader, VuDroid. As a software engineering process called Spiral Model was applied to the project, a chapter brings up how this affected work. Information regarding the implementation choices and a few problems that arose during the coding process as well as the solutions to them can also be found within. The result is an application that can read PDF-files, present them for the user and have the ability to add a layer with text and drawings. The resulting application and work process is evaluated at the end of the project report.
Keywords: Data- och informationsvetenskap; Datavetenskap (datalogi); Computer and Information Science; Computer Science